The golden liquid and criminal opportunity - Azlinda Abdul Samad; Abdul Samad Abdul Ghani (Penerbit Universiti Kebangsaan Malaysia, 2022)
The situation of the COVID-19 pandemic resulted in the whole world scrambling to find a vaccine that could help contain the pandemic that is raging. This is because COVID-19 vaccines are seen as the best possible solution for containing the virus in the current situation. However, once the vaccines for COVID-19 received approval for use, the high demand for this new ‘liquid gold’ has resulted in some unscrupulous parties taking advantage of the situation by committing organised crime with the intention of profiting from the vaccines. As a result, there are now threats of substandard and counterfeit vaccines in the supply chain. The high demand for the vaccines globally and the limited supplies have further spurred this criminal intent. Additionally, the desperation among the global population to get a hold of the COVID-19 vaccines has seen the online platform being used as the medium for perpetrating these criminal activities. The allocation and distribution of the vaccines are also unprecedented because of the global scale of the pandemic and many countries are rushing to get their population vaccinated in the hope of curtailing the virus. Thus, the risk of corruption may take place at any stage of the allocation and distribution process, and eventually, this could pose serious threats to public health goals. For this reason, these threats must be identified, mitigated and handled carefully. Co-operation, communication and networking among the relevant bodies and the pharmaceutical industry are therefore vital. Additionally, law enforcement agencies need to be prepared and ready for any unanticipated circumstance. Governments must be transparent and accountable, and governance must be put in place. Awareness among all parties involved is indeed crucial but most importantly, the public must be educated on the risk of purchasing COVID-19 vaccines online.